Physicochemical quality of oily wastewater from automotive workshop in Kota Bharu, Kelantan Malaysia - Marina Bujang; Noor Azlina Ibrahim; Aweng Eh Rak (2012)
Increase in the number of motor vehicle workshops around Kota Bharu has resulted in water pollution problems occur in this area. To prove this hypothesis is correct, a study was conducted where oily wastewater samples were collected from three different automotive workshops in Kota Bharu area. All the three workshops were identified as workshop K, P and T. The sampling was performed three times which were in February 2010, May 2010 and November 2011. The collected samples were analyzed for pH (4.24 - 7.57), temperature (27.2 - 29.8 ℃), biochemical oxygen demand (57.8 - 318.2 mg/L), chemical oxygen demand (137 - 9881 mg/L)), dissolved oxygen (0.15 - 9.42 mg/L)), and oil and grease (14.2 - 90,500 mg/L). The lowest dissolved oxygen was recorded in May 2010 at automotive workshops K. Meanwhile, the highest biochemical oxygen demand and chemical oxygen demand were recorded in February 2010 at automotive workshop T (318.2 ± 1.89 mg/L) and in May 2010 at automotive workshops P (9881 ± 7.46 mg/L) respectively. The results showed that, all the parameters excepted pH and temperature were high and exceeded permissible level (Standard B) listed in the Third Scheduled, Environmental Quality (Sewage and Industrial Effluents) Regulations, 1979 of Environmental Quality Act, 1974.